Genome‐wide association analysis of actigraphic sleep phenotypes in the LIFE Adult Study. (29th April 2016) - Spada, Janek; Scholz, Markus; Kirsten, Holger; Hensch, Tilman; Horn, Katrin; Jawinski, Philippe; Ulke, Christine; Burkhardt, Ralph; Wirkner, Kerstin; Loeffler, Markus; Hegerl, Ulrich; Sander, Christian
Summary: The genetic basis of sleep is still poorly understood. Despite the moderate to high heritability of sleep‐related phenotypes, known genetic variants explain only a small proportion of the phenotypical variance. However, most previous studies were based solely upon self‐report measures. The present study aimed to conduct the first genome‐wide association (GWA) of actigraphic sleep phenotypes. The analyses included 956 middle‐ to older‐aged subjects (40–79 years) from the LIFE Adult Study. The SenseWear Pro 3 Armband was used to collect 11 actigraphic parameters of night‐ and daytime sleep and three parameters of rest (lying down). The parameters comprised measures of sleep timing, quantity and quality. A total of 7 141 204 single nucleotide polymorphisms (SNPs) were analysed after imputation and quality control. We identified several variants below the significance threshold of P ≤ 5× 10 −8 (not corrected for analysis of multiple traits). The most significant was a hit near UFL1 associated with sleep efficiency on weekdays ( P = 1.39 × 10 −8 ). Further SNPs were close to significance, including an association between sleep latency and a variant in CSNK2A1 ( P = 8.20 × 10 −8 ), a gene known to be involved in the regulation of circadian rhythm. In summary, our GWAS identified novel candidate genes with biological plausibility being promising candidates for replication and further follow‐up studies.